2007
DOI: 10.1038/sj.pcan.4500934
|View full text |Cite
|
Sign up to set email alerts
|

Bicalutamide 80 mg combined with a luteinizing hormone-releasing hormone agonist (LHRH-A) versus LHRH-A monotherapy in advanced prostate cancer: findings from a phase III randomized, double-blind, multicenter trial in Japanese patients

Abstract: To compare combination therapy with bicalutamide 80 mg and a luteinizing hormone-releasing hormone agonist (LHRH-A) versus LHRH-A alone in Japanese men with untreated advanced prostate cancer. A total of 205 patients with stage C/D prostate cancer were randomized to either LHRH-A þ once-daily oral bicalutamide 80 mg or placebo. Primary study variables have been reported previously. Secondary variables included: time to achieve prostate-specific antigenp4 ng/ ml, time-to-treatment failure (TTTF), time-to-diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 15 publications
2
45
0
Order By: Relevance
“…The MAB group was significantly superior in terms of anti-tumor effects, TTP and TTF without increasing toxicity or QOL deterioration. Moreover, according to the final results (median follow-up of 127 weeks) reported by Usami et al [54], the superiority of the MAB group in terms of TTP and TTF was even more marked than the interim analysis. However, OS and causespecific survival as the secondary endpoints were not significant between the groups because of a lack of death events.…”
Section: A Combined Androgen Blockadementioning
confidence: 99%
See 1 more Smart Citation
“…The MAB group was significantly superior in terms of anti-tumor effects, TTP and TTF without increasing toxicity or QOL deterioration. Moreover, according to the final results (median follow-up of 127 weeks) reported by Usami et al [54], the superiority of the MAB group in terms of TTP and TTF was even more marked than the interim analysis. However, OS and causespecific survival as the secondary endpoints were not significant between the groups because of a lack of death events.…”
Section: A Combined Androgen Blockadementioning
confidence: 99%
“…The largest study, the EPC (Early Prostate Cancer) program [54] has randomized > 8000 patients with localized or locally advanced prostate cancer to bicalutamide alone versus placebo after they had been treated with surgery or radiation therapy. At a follow-up of > 7 years, bicalutamide had a positive impact on TTP but was unable to provide any significant survival benefit compared to placebo.…”
Section: Antiandrogen Monotherapymentioning
confidence: 99%
“…In this situation, it is important to precisely evaluate the clinical efficacy of ADT consisting of traditional maximum androgen blockade (MAB) at this time. There have been several reports of outcomes from patients with prostate cancer treated with ADT [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]; however, the number of studies, that reported outcomes in patients with bone metastatic prostate cancer treated primarily with MAB without any local treatment, is limited. Recently, outcomes of MAB as an initial treatment for patients with bone metastatic prostate cancer have been reported, in which the significant impact of PSA kinetics not on OS but on disease progression was demonstrated [16].…”
Section: Open Accessmentioning
confidence: 99%
“…Some recent studies have shown better outcomes in patients treated with CAB compared with LHRH agonist monotherapy. [28][29][30] However, a metaanalysis and randomized placebo-controlled clinical trial have revealed that the difference between LHRH agonist and CAB was only of a few percentage or nothing. 31,32 Therefore, the initial treatment strategy within the present step-up for hormonal therapy may be reasonable in clinical settings.…”
Section: 9%mentioning
confidence: 99%